Pendampingan Fikih Marital bagi Remaja Putus Sekolah - Bashori Alwi; Muhtamilatur Rohmah; Moh. Shidqie Muhtadi; Nuril Azizu Anggraini; Siti Yusrohlana; Devi Yunilasari; Nurmasita Nurmasita (GUYUB: Journal of Community Engagement, 2021)
Divorce has always been a phobia for married couples. The causes are almost the same, if not for economic factors, of course due to the lack of knowledge and ethics in the family. Therefore, this community service is carried out to reduce the number of divorces due to these three factors in Karanganyar Paiton village and Asembakor Kraksaan village, Probolinggo. The mentoring process uses the Participatory Action Research (PAR) approach, which begins with mapping the problem (diagnosis), planning movement (mapping), carrying out transformative movements (action), observing and evaluating (observe), and compiling theoritization (reflect). The results of this community service are; 1) provide awareness to the public about the importance of marital fiqh education and economic readiness in forming a harmonious family; 2) this activity also resulted in the formation of a family counseling center that can be used by the general public to share, consult and resolve family problems.